The thief collector [videorecording (DVD)] - Wohl, Daniel, 1980- (MVD Visual ; FilmRise, 2023)
In 1985, Willem de Kooning's oil painting Woman-Ochre vanished from the University of Arizona Museum of Art in Tucson. The $160 million work of art remained missing until 2017, when it was found hanging in the former home of Jerry and Rita Alter, a deceased New Mexico married couple. The film features interviews with the Alters' family members and those involved in the painting's disappearance and recovery. The film also utilizes actors to stage reenactments of the theft, as well as adaptations of short stories from a book written by Jerry Alter. -- Provided by publisher.